Deacetylation of LAMP1 drives lipophagy‐dependent generation of free fatty acids by Abrus agglutinin to promote senescence in prostate cancer. Issue 3 (23rd September 2019) - Panda, Prashanta Kumar; Patra, Srimanta; Naik, Prajna Paramita; Praharaj, Prakash Priyadarshi; Mukhopadhyay, Subhadip; Meher, Biswa Ranjan; Gupta, Piyush Kumar; Verma, Rama S.; Maiti, Tapas K.; Bhutia, Sujit K.
Abstract: Therapy‐induced senescence in cancer cells is an irreversible antiproliferative state, which inhibits tumor growth and is therefore a potent anti‐neoplastic mechanism. In this study, low doses of Abrus agglutinin (AGG)‐induced senescence through autophagy in prostate carcinoma cells (PC3) and inhibited proliferation. The inhibition of autophagy with 3‐methyl adenine reversed AGG‐induced senescence, thus confirming that AGG‐triggered senescence required autophagy. AGG treatment also led to lipophagy‐mediated accumulation of free fatty acids (FFAs), with a concomitant decrease in the number of lipid droplets. Lalistat, a lysosomal acid lipase inhibitor, abrogated AGG‐induced lipophagy and senescence in PC3 cells, indicating that lipophagy is essential for AGG‐induced senescence. The accumulation of FFAs increased reactive oxygen species generation, a known facilitator of senescence, which was also reduced in the presence of lalistat. Furthermore, AGG upregulated silent mating type information regulator 2 homolog 1 (SIRT1), while the presence of sirtinol reduced autophagy flux and the senescent phenotype in the AGG‐treated cells. Mechanistically, AGG‐induced cytoplasmic SIRT1 deacetylated a Lys residue on the cytoplasmic domain of lysosome‐associated membrane protein 1 (LAMP1), an autolysosomal protein, resulting in lipophagy and senescence. Taken together, our findings demonstrate a novel SIRT1/LAMP1/lipophagy axis mediating AGG‐induced senescence in prostate cancer cells. Abstract : Therapy induced senescence by Abrus agglutinin (AGG) requires autophagy. Silent mating type information regulation 1 (SIRT1) regulates AGG‐induced autophagy and senescence. SIRT1 deacetylates lysosome‐associated membrane protein 1 (LAMP1) to induce lipophagy. Lipophagy‐dependent free fatty acid (FFA) accumulation promotes reactive oxygen species (ROS) to influence senescence